The Analysis Study of Prevalence of Gastrointestinal Complication in Patients with Type 2 Diabetes Mellitus : A Comprehensive Systematic Review - Rahman, Fahmi Fathul; Istiana, Septa (International Medical Journal Corp. Ltd, 2024)
Background: Diabetes, a chronic metabolic disorder, has a high prevalence worldwide due to changing lifestyles and urbanization. It is associated with life-threatening hazards and disabling complications, decreasing life expectancy. Gastroparesis, a well-known manifestation, is more prevalent in women. Understanding the prevalence of gastrointestinal complications in type 2 diabetes mellitus patients is crucial for creating effective treatment regimens. Methods: Adhering to the PRISMA 2020 principles, this systematic study focused on analyzing complete English literature texts published from 2011 to 2024. Several websites, such as ScienceDirect, PubMed, and SagePub, were used to collect the literature. Result: The study examined over 4000 publications sourced from recognized platforms such as Science Direct, SagePub, and PubMed. Following the decision to subject eight publications to further scrutiny, a comprehensive examination of the complete body of literature was conducted. Conclusion: Diabetes often leads to gastroparesis, a condition affecting the upper gastrointestinal tract, associated with metabolic imbalance, high blood sugar levels, low insulin, hormone release, and H. pylori infection. This condition is linked to the contractile activity of the duodenum, and is associated with various liver conditions, including diabetic fibrosis and cirrhosis.